Cleo: 2014 2014
DOI: 10.1364/cleo_qels.2014.ftu2c.2
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Tunable Photonic Hyper-Crystals

Abstract: We demonstrate a novel artificial optical material, the ''photonic hyper-crystal'', which combines the most interesting features of hyperbolic metamaterials and photonic crystals. Similar to hyperbolic metamaterials, photonic hyper-crystals exhibit broadband divergence in their photonic density of states due to the lack of usual diffraction limit on the photon wave vector. On the other hand, similar to photonic crystals, hyperbolic dispersion law of extraordinary photons is modulated by forbidden gaps near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Therefore, photonic hyper-crystals exhibit light localization on deep subwavelength scales, which far exceeds the demonstrated mode volume reduction in photonic crystals. It was suggested that such strong field localization would lead to considerable enhancement of nonlinear optical effects in photonic hyper-crystals [3]. In this paper we will demonstrate that the level of nonlinearities achievable in photonic hyper-crystals indeed looks very promising for optical limiting and optical computing applications.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Therefore, photonic hyper-crystals exhibit light localization on deep subwavelength scales, which far exceeds the demonstrated mode volume reduction in photonic crystals. It was suggested that such strong field localization would lead to considerable enhancement of nonlinear optical effects in photonic hyper-crystals [3]. In this paper we will demonstrate that the level of nonlinearities achievable in photonic hyper-crystals indeed looks very promising for optical limiting and optical computing applications.…”
Section: Introductionmentioning
confidence: 68%
“…Strong Bragg scattering is observed near the Brillouin zone boundaries at k z ~ /L >> , leading to the formation of photonic bandgaps in both the wavenumber and the frequency domains. An example of the band structure calculations and a Bloch mode profile for a linear photonic hyper-crystal may be found in [3].…”
Section: Linear Optical Properties Of Hyperbolic Resonator-based Photmentioning
confidence: 99%
See 1 more Smart Citation
“…It is this type of hyperbolic media that holds the most promise for practical applications of the concept of the hypercrystal [54].…”
Section: B "Real-world" Hypercrystalsmentioning
confidence: 99%
“…Prominent examples include light-induced collective orientation of liquid crystal molecules [31], pressure induced control of lasing frequency in a 1D array of droplets [32], magnetic induced ferrofluid-based hyperbolic metamaterial [33], and chemical composition induced changes enabling lasing frequency tuning in 1D systems [34] and in 2D photonic crystals [35]. Furthermore, recent studies introduced a novel interaction between SPPs and a thin liquid dielectric (TLD) film due to geometrical changes of the gas-fluid (or fluid-fluid) interface, facilitated arXiv:1912.06179v1 [physics.optics] 12 Dec 2019 by the thermocapillary (TC) effect; theoretical study of self-induced focusing and defocusing effects of propagating SPPs due to nonlocal interaction [36] (where refractive index changes extend beyond the regions of maximal optical intensity) as well as formation of an optical liquid lattice of a fixed square symmetry, and experimental demonstration of TC-assisted optical tuning of surface plasmon resonance coupling angle [37].…”
mentioning
confidence: 99%